Synergistic effect of MgH2 doping with Ni and carbon nanotubes on thermochemical CO2 recycling process for CH4-H2 mixtures production. (1st January 2022) - Amica, Guillermina; Gennari, Fabiana C.
Abstract: The synergistic effect of the nickel and carbon nanotubes addition on thermochemical processes for CO2 recycling employing MgH2 as hydrogen source was demonstrated. By reducing the metallic charge from 10wt.% Ni, replacing 5wt.% with CNTs, the amount of produced methane through thermal treatment at ∼350–375 °C under CO2 increased more than 30%. A COx -free mixture of methane (70.9%) and hydrogen (29.1%) with a CH4 yield of 79% was obtained by reaction at 350 °C during 48 h. Ni-containing species act as selective catalyst promoting the occurrence of the Sabatier reaction, which competes with the direct reduction of CO2 to generate CH4 via C as an intermediary. The role of CNTs is not catalytic but rather it could be related to the protection of the hydride. It is proposed that when MgH2 is neighbored by graphitic planes, its oxidation due to direct contact with CO2 and/or the generated H2 O could be impeded or retarded. Graphical abstract: Image 1 Highlights: CO2 was transformed to CH4 by thermochemical processes using MgH2 as hydrogen source. Ni and CNTs addition to MgH2 has a synergetic effect on CH4 yield. COx-free mixture of CH4 :H2 were produced from CO2 conversion at 350 °C. Ni-containing species are selective catalysts that promote the Sabatier reaction. CNTs might act as hydride protection retarding its oxidation.